Sovereign Default Risk Premia and State-Dependent Twin Deficits - Patrick Hürtgen; Ronald Rühmkorf (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper studies the impact of the state-dependent risk of a government default on the correlation of the scal balance and current account. We use a small open economy model where nonlinear risk premia arise endogenously when the government operates close to its scal limit, i.e. the maximum capacity of a country to repay its debt. The presence of the possible sovereign default leads to dynamics of sovereign debt which cause taxes to rise and increase the dispersion of resulting tax levels. In line with data for industrialized countries household saving increases at high debt-to-GDP levels and the correlation of the scal balance and current account decreases. We calibrate the model to Greece and simulate the debt crisis as a result of negative TFP shocks and nd that the model dynamics t to the data.
Keywords: E62; F32; H31; 330